Peran Guru Akidah Akhlak Dalam Membimbing Peserta Didik Agar Lebih Berkarakter Di MIS Al Fikri Kamama Mekar - Usman Usman; Dian Dian; Indah Fitrianti; Rhodiyatul Jasiyah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
This study aims to find aind about the efforts of Aqidah Moral teachers in instilling studets moral values, and what moral values are instilled by Aqidah Akhlak teachers in their students, and also what factors are the constraints of moral aqidah teachers in instilling moral values. Towards fifth grade students Mis Al Fikri, Kamama Mekar Village, Gu District, Central Buton Regency The method used in this study is a qualitative research method with a descriptive approach, namely describing various events and information obtained during the research. The subjects in this study were aqidah akhlak teachers and fifth grade students Mis Al Fikri, Kamama Mekar Village, as for data collection, namely observation, documentation, and interviews. The results obtained in this study are the way in which the teacher`s aqidah akhlak instills moral values, namely through effective learning. The teacher becomes a role model for studets and the teacher familiarizes students with good things. The moral values that are instilled by the teacher of aqeedah morals are about being honest, politeness and discipline, while the factors faced by teachers off aqeedah morals are technological factors that are developing rapidly at this time the awareness students own as well as environmental factors.